Prevalence Proportion of Patient with Coronary Heart Disease in Inpatient Room of RSUD Dr. Soetomo Surabaya in 2017 - Faradila Budi Saputri; Dyah Fauziah; Esti Hindariati (Biomolecular and Health Science Journal, 2020)
Introduction: Coronary heart disease (CHD) is the most common type of heart disease that causes death. It occurs as a result of hardening of the coronary arteries which supply oxigen-rich blood to the entire heart muscle so that the heart can contract properly. However, many patients neglect the symptoms. Moreover, the risk factor and the comorbides disease worsen the condition. This research aims to study the profile of coronary heart disease patients in the inpatient rooms at Dr. Soetomo General Hospital Surabaya in 2017.Methods: This study was a cross-sectional and retrospective study by assessing patients’ medical record and analyzed descriptively.Results: From total 587, 263 patiens met inclusion criteria, aged between 51-60 years (42.6%) with domination of male (82,13%). %). Risk Factors are into one of the Comorbidities of CHD Patient. There are Risk Factor can be aggravate of CHD Patients. Most of subjects had risk factor hipertension (50,79%), and hypertension with DM (38,7%). Hypertension based on systolic pressure and diastolic pressure obtained that systolic pressure <120 mmhg was 39.6% and diastolic pressure <80 was 37.4%.Conclusion: Most of CHD patients in this study were in age group 51 – 60 years old, male, had risk factor hypertension and DM.